The effect of thymopentin add-on in hepatitis B e antigen positive chronic hepatitis B after virus suppression by peginterferon plus entecavir therapy - Ma, Yanpin; Bao, Xuli; Xiong, Fang; Wang, Jinhuan; Gu, Na; Guo, Jia; Wu, Huili; Lu, Jun (Cellular and Molecular Biology, 2019)
Hepatitis B virus (HBV) covalently closed circular DNA (cccDNA) was positively correlated with serological hepatitis B surface antigen (HBsAg) levels in hepatitis B e antigen (HBeAg) positive chronic hepatitis B (CHB) patients. We evaluated whether Thymopentin (TP5) and interferon (IFN-a) had a synergic effect on HBV cccDNA and the effect of TP5 addition therapy on HBsAg clearance in CHB patients. Real-time PCR experiments were performed to test cccDNA in HepG2.2.15 cells. 45 HBeAg-positive CHB patients had been distributed into two groups randomly. Treatment group: 23 patients were treated with a 24-week TP5 on the basis of the treatment entecavir (ETV) and peginterferon alfa-2a (PegIFN alpha-2a). Control group: 22 patients were treated with ETV and PegIFNa-2a. The study period was 72 weeks. In HepG2.2.15 cells, TP5 5ug/ml and 10ug/ml respectively combined with IFN-a 2ku/ml could potently inhibit cccDNA level at 72 hours (P<0.05). In clinical study, mean HBsAg levels in two groups are not significantly different at different time points (p=0.112). However, changes of mean HBsAg levels in TP5 add-on group at different time points are significantly different (p<0.05). Patients with HBsAg levels <1500IU/ml in control group had higher HBsAg levels compared with patients with HBsAg levels <1500IU/ml in TP5 add-on group (P=0.019). The latter had the most pronounced HBsAg reduction. TP5 and IFN had a synergic effect on inhibiting cccDNA levels in HepG2.2.15 cells; Patients in treatment group showed no extra side effects compared with the control group. 24 weeks TP5 add-on treatment was safe and had a tendency to accelerate the decline of HBsAg when HBV-DNA was undetectable.